1999
DOI: 10.1037/0882-7974.14.4.627
|View full text |Cite
|
Sign up to set email alerts
|

Everyday cognition: Age and intellectual ability correlates.

Abstract: The primary aim of this study was to examine the relationship between a new battery of everyday cognition measures, which assessed 4 cognitive abilities within 3 familiar real-world domains, and traditional psychometric tests of the same basic cognitive abilities. Several theoreticians have argued that everyday cognition measures are somewhat distinct from traditional cognitive assessment approaches, and the authors investigated this assertion correlationally in the present study. The sample consisted of 174 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
230
1
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 158 publications
(242 citation statements)
references
References 66 publications
(167 reference statements)
9
230
1
2
Order By: Relevance
“…For the ECB Inductive Reasoning test, participants had to generate answers, and for the ECB Declarative Memory and Knowledge tests, participants had to recognize answers. Results from previous analysis with the full parent sample from which this study is drawn (Allaire & Marsiske, 1999) indicated that the internalconsistency reliability of each ECB test was adequate, with Cronbach alpha estimates ranging from .69 to .88. Additional information regarding the content, structure, and psychometric characteristics of the ECB tests are provided in Allaire and Marsiske (1999).…”
Section: Well-defined Everyday Cognition Measuresmentioning
confidence: 80%
See 3 more Smart Citations
“…For the ECB Inductive Reasoning test, participants had to generate answers, and for the ECB Declarative Memory and Knowledge tests, participants had to recognize answers. Results from previous analysis with the full parent sample from which this study is drawn (Allaire & Marsiske, 1999) indicated that the internalconsistency reliability of each ECB test was adequate, with Cronbach alpha estimates ranging from .69 to .88. Additional information regarding the content, structure, and psychometric characteristics of the ECB tests are provided in Allaire and Marsiske (1999).…”
Section: Well-defined Everyday Cognition Measuresmentioning
confidence: 80%
“…Comparisons between the current sample and the subsample of participants who completed the OEEPT (n ϭ 130) and those participants in the larger sample who did not (n ϭ 44) indicated that the two groups did not significantly differ in age, t (172) ($14,905). A detailed description of the parent sample (N ϭ 174) is provided in Allaire and Marsiske (1999). Participants received a small honorarium ($20) for their participation.…”
Section: Samplementioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, Whitfield (1996Whitfield ( , 2002 suggested that studies should examine the practical aspects of cognitive functioning, including performance on measures of everyday problem solving, in the assessment of cognitive status. In general, everyday problem solving measures, by assessing cognition within contextually relevant domains (i.e., medication use, transportation, and other instrumental activities of daily living), have been thought to have more ecological value in determining older adults' daily functioning, than traditional cognitive measures (Allaire & Marsiske, 1999;Willis, 1991).…”
Section: The Role Of Education In Cognitive Performancementioning
confidence: 99%